La Regulación Jurídica de la Fecundación Asistida Dentro del Matrimonio y Unión de Hecho como Alternativa para Superar Problemas Genéticos que Embaracen la Convivencia Familiar - Paz Rivera, Erika Josselin (2016)
The present research untitled “The juridical regulation of the assisted fertilization inside the marriage and union of fact as an alternative to overcome genetic problems that embarrass the familiar life” refers to the absence of evolution in the Ecuadorian legislation, in agreement with the trends in the field of science and technology The purpose of my investigation is to clarify that procreation has been affected throughout the years by problems of sterility and infertility, causing problems in the conviviality of the pair; nevertheless, over the years and thanks to big investigators, it has been achieved to overcome this obstacle. I mention the relation between ethic and right, the natural conception of bio-juridical and its application in our juridical classification, because it’s evident that exist juridical emptinesses in the case of human assisted reproduction methods and their utilization as an alternative. The consequences of not possessing an only and specific law for the application of assisted fertilization techniques can change depending of the field in which it places; an evident deficiency is the filiation, the regulation of the Fertilization Centers and the manipulation of embryos. 5 In Ecuador, the cases of assisted reproduction have gone in increase, every time they are more persons who come to the Fertilization Centers with the hope to bring a new life to their lives; nevertheless, these persons are not protected juridically, they need a norm that look after their rights and control their obligations. My investigation rests principally in the field investigation realized, which allowed me to compile information by surveys realized to law professionals; and, the interviews directed to specialists doctors in forensic medicine and university teachers.